Keamanan Jurnalis Sebagai Isu Sumber Daya Manusia Strategis : Analisis Data 2024 untuk Reformasi Manajemen Media - Zandra Dwanita Widodo (Universitas Veteran Bangun Nusantara, 2025)
The issue of journalist safety in Indonesia is increasingly urgent to be studied within the framework of strategic human resource management (HR). The work risks faced by journalists not only reflect external pressure from third parties but also indicate the weakness of the internal protection system implemented by media organizations. This study aims to analyze the perception and experience of journalist safety risks and evaluate the role of individual characteristics, organizational responses, and legal support in creating safe and sustainable working conditions. The research method used is a quantitative descriptive approach by utilizing secondary data from the 2024 Journalist Safety Index (IKJ). The data includes 760 journalist respondents from various regions in Indonesia, which were analyzed using frequency distribution techniques, cross tabulations, and simple correlations. The main variables consist of individual journalist characteristics (X1), media organization responses (X2), external legal support (X3), and safety risks (Y1), perceptions of protection (Y2), and psychological resilience (Y3). The results of the study show that female journalists, low-income journalists, and journalists domiciled outside Java have higher levels of risk. The response of media organizations to safety issues is still relatively weak, especially in terms of safety training and provision of protection protocols. Meanwhile, the available legal support is not yet fully effective, but still plays a role in increasing the courage of reporting and the psychological stability of journalists. The conclusion of this study confirms that journalist safety must be an integral part of the media HR management system. Institutional reform, including strengthening internal regulations, legal assistance, and risk-based training, are strategic steps that need to be implemented to build a professional and safe media ecosystem.